Warlight [compact disc, unabridged] - Ondaatje, Michael, 1943- (Random House Audio, Inc., 2018)
In 1945, fourteen-year-old Nathaniel and his older sister Rachel stay behind in London when their parents move to Singapore, leaving them in the care of a figure they suspect might be a criminal.